Reshaping of the gastrointestinal microbiome alters atherosclerotic plaque inflammation resolution in mice - Michael S. Garshick (Nature Portfolio, 2021)
Abstract Since alterations in the intestinal microbiota may induce systemic inflammation and polarization of macrophages to the M1 state, the microbiome role in atherosclerosis, an M1-driven disease, requires evaluation. We aimed to determine if antibiotic (Abx) induced alterations to the intestinal microbiota interferes with atherosclerotic plaque inflammation resolution after lipid-lowering in mice. Hyperlipidemic Apoe −/− mice were fed a western diet to develop aortic atherosclerosis with aortas then transplanted into normolipidemic wild-type (WT) mice to model clinically aggressive lipid management and promote atherosclerosis inflammation resolution. Gut microbial composition pre and post-transplant was altered via an enteral antibiotic or not. Post aortic transplant, after Abx treatment, while plaque size did not differ, compared to Apoe −/− mice, Abx– WT recipient mice had a 32% reduction in CD68-expressing cells (p = 0.02) vs. a non-significant 12% reduction in Abx+ WT mice. A trend toward an M1 plaque CD68-expresing cell phenotype was noted in Abx+ mice. By 16S rRNA sequence analysis, the Abx+ mice had reduced alpha diversity and increased Firmicutes/Bacteroidetes relative abundance ratio with a correlation between gut Firmicutes abundance and plaque CD68-expressing cell content (p < 0.05). These results indicate that in a murine atherosclerotic plaque inflammation resolution model, antibiotic-induced microbiome perturbation may blunt the effectiveness of lipid-lowering to reduce the content of plaque inflammatory CD68-expressing cells.